The Serine/Threonine-Protein Phosphatase 1 From Haemonchus contortus Is Actively Involved in Suppressive Regulatory Roles on Immune Functions of Goat Peripheral Blood Mononuclear Cells - Ehsan, Muhammad; Wang, WenJuan; Gadahi, Javaid Ali; Hasan, Muhammad Waqqas; Lu, MingMin; Wang, YuJian; Liu, XinChao; Haseeb, Muhammad; Yan, RuoFeng; Xu, LiXin; Song, XiaoKai; Li, XiangRui (Frontiers in Immunology, 2018)
Serine/threonine protein phosphatases, as integral constituents of parasitic excretory/secretory proteins (ESPs) are assumed to be released during the host-parasite interactions. However, knowledge about these phosphatases and their immunoregulatory and immune protective efficiencies with host PBMCs is scant. In the present study, an open reading frame (ORF) of H. contortus serine/threonine protein phosphatase designated as HcSTP-1 was amplified and cloned from H. contortus cDNA by reverse transcription-polymerase chain reaction (RT-PCR). The 951 bp nucleotides encoded a predicted protein of 316 amino acids, conserved in characteristic motifs GDXHG, GDYVDRG, GNHE, HGG, RG, and H. The HcSTP-1 protein was expressed in the Escherichia coli strain BL21, which was 35 kDa as recombinant protein fused with the vector protein of 18 kDa on SDS-PAGE. Immunohistochemically, HcSTP-1 was found to be localized in both male and female adult worm sections. The binding activity of rHcSTP-1 on surface of goat peripheral blood mononuclear cells (PBMCs) was confirmed by immunofluorescence assay (IFA), which resulted in expression of multiple cytokines and various immunomodulatory activities in vitro. The real time PCR results showed that mRNA level of IL-2, TGF-β1, IFN-γ and IL-17 (with 10µg/ml), were up-regulated and IL-10 was decreased, however, IL-6 showed no change after PBMCs incubated with rHcSTP-1 protein. Further functional analysis showed that cell migration, nitric oxide (NO) production and apoptotic efficiency of PBMC were elevated at significant level, whereas the proliferation of goat PBMCs and major histocompatibility complex (MHC) both class I and II in monocytes were decreased significantly at concentration dependent fashion. Our results showed that the HcSTP-1 protein played important suppressive regulatory roles on the goat PBMCs, which might represent a potential molecular target for controlling H. contortus infection in future.